Exhale (shoop shoop) - Houston, Whitney; Babyface; Twentieth Century Fox Film Corporation (New York : Twentieth Century Fox Film Corporation, 1995)
Contains the track taken from Waiting To Exhale Original Soundtrack Album.
CD 1 : Exhale (Shoop Shoop) / (3:24).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English